2020
DOI: 10.1101/2020.11.24.20237156
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations between alcohol use and accelerated biological ageing

Abstract: BackgroundHarmful alcohol use is a leading cause of premature death, and is associated with age-related disease. Ageing is highly variable between individuals, and may deviate from chronological ageing, suggesting that biomarkers of biological ageing (based on DNA methylation or brain structural measures) may be clinically relevant. Here, we investigated the relationships between alcohol phenotypes and both brain and DNA methylation age estimates.MethodsFirst, using data from UK Biobank and Generation Scotland… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…We explored whether the relationship between SA and GrimAgeAccel was attenuated when covarying for these indexes of severity (Tables 4 and S5) and found that substance abuse may account for some of the higher GrimAgeAccel observed with SA. Previous studies have documented the association between substance abuse and accelerated aging [58,59].…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
“…We explored whether the relationship between SA and GrimAgeAccel was attenuated when covarying for these indexes of severity (Tables 4 and S5) and found that substance abuse may account for some of the higher GrimAgeAccel observed with SA. Previous studies have documented the association between substance abuse and accelerated aging [58,59].…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
“…Their findings provide evidence that smoking causally increases the occurrence of white matter hyperintensities, suggesting that smoking accelerates brain ageing (alcohol was not studied). Another MR study investigated effects of alcohol consumption and hazardous alcohol use on a composite measure of predicted brain age [4]. They found consistent evidence that higher alcohol consumption causally increases brain age, and limited evidence that alcohol use disorder has similar effects (with the cautionary note that the latter was largely driven by a single genetic variant).…”
mentioning
confidence: 99%